Evidence of extensive mitochondrial introgression with nearly complete substitution of the typical Squalius pyrenaicus-like mtDNA of the Squalius alburnoides complex (Cyprinidae) in an independent Iberian drainage - Santos, Carla Sousa (2012)
The first occurrence of massive mitochondrial introgression of Squalius aradensis genes in Squalius alburnoides, a hybridogenetic complex that usually carries mtDNA of its maternal ancestor (Squalius pyrenaicus) is reported. Possible implications of such introgressions for the history of the complex are discussed.